As relações étnico-raciais na escola de educação básica: exigências e desafios das Leis 10.639/2003 e 11.645/2008 - Bueno, Francisca Izabel da Silva (2023)
This dissertation analyzes the justifications, principles, propositions and challenges arising from the implementation of Laws 10,639/03 and 11,645/08, which establish the obligation to study Afro, Afro-Brazilian and Indigenous History and Culture, in schools of elementary and secondary education in Brazil. The investigation interrogates the reasons and principles that support the proposition of including studies on the history and culture of African and Afro-Brazilian peoples and the recognition of their contribution to the formation of national identity and the fight against racism. In view of this, the general objective is to analyze the requirements and challenges arising from federal laws 10.639/03 and 11.645/08, with regard to the training to be developed in basic education schools regarding the study of Afro and Afro-Brazilian History and Culture. and Indigenous. The structure of the text pays attention, in a first topic, to the process of construction of legislation, highlighting the participation of black movements and other movements. Using a timeline analysis as support, the reasons for the absence of African history and culture in schools are explained as a result of colonialism, which supported racism and prevented, for centuries, the recognition of the originality and protagonism of African and Afro-Brazilian. This initial reflection includes contributions from Fanon, Bâ, Mbembe, Munanga, Freire, Cavalleiro, Gomes, Pereira, among others. In the following topic, the text focuses on the analysis of some basic aspects of the two federal laws - 10.639/03 and 11.645/08 - the challenges of their construction, the justifications and guiding principles, the mobilizations, struggles and initiatives that made the promulgation of these laws possible, highlighting, especially, the contribution of black movements organized around this struggle. The last topic presents and reflects on some initiatives and projects that have been and are being proposed and developed in an attempt to implement an ethnic-racial education guided by the knowledge and principles of African and Afro-Brazilian culture, seeking to understand their uniqueness and highlight their importance in promoting integral human formation and repairing the injustice historically promoted against black men and women. The conclusion demonstrates the importance of laws and guidelines as part of the struggles of black movements, but, however, highlights the persistence of major challenges in the face of the continuity of racist practices and the limited recognition of the importance of the culture and history of Afro and African peoples. -Brazilians in human formation.